How Shanghai Does It : Insights and Lessons from the Highest-Ranking Education System in the World - Liang, Xiaoyan; Kidwai, Huma; Zhang, Minxuan (Washington, DC: World Bank, 2016)
The Shanghai basic education system has garnered significant attention since its extraordinary performance in the 2009 and 2012 Programme for International Student Assessment (PISA), a global assessment of 15-year-olds’ educational abilities. Among the 65 participating economies in 2012, Shanghai-China ranked first on all three major domains of PISA, i.e. mathematics, reading, and science. Shanghai also stands out for having the world’s highest percentage of “resilient students”, students from socio-economically disadvantaged backgrounds who emerge as top performers. Shanghai’s PISA story has generated intense discussions and diverse speculations in field of international educational development, and numerous studies have been done in the attempt to unravel the mystery. Missing from the picture however is a more comprehensive, systematic, in-depth, and objective rendition of the policies and practices of Shanghai basic education, benchmarked against others in key dimensions.